Stunting - Hanswanti Putri Niasti Nauli Lase; Inda M. H. Sinaga (Jurnal Kedokteran Methodist, 2025)
Background: Stunting, or failure to thrive, is a chronic nutritional condition resulting from prolonged inadequate nutrient intake. In the short term, stunting can increase morbidity; in the long term, it manifests as delayed bone growth and low body weight. Children with stunting are significantly shorter than their peers. Objective: This study aims to identify the multifaceted risk factors contributing to stunting. Discussion: Stunting is influenced by a complex interplay of environmental and genetic factors. Key environmental determinants include maternal nutritional status, child feeding patterns, and environmental sanitation. While hereditary factors and hormonal imbalances play a role, malnutrition remains a primary preventable cause of short stature in children. Conclusion: Understanding both environmental and genetic factors is crucial for the effective prevention of stunting and the improvement of children’s nutritional health.